Aflibercept as a second-line therapy in metastatic colorectal cancer: A limited Indian experience - Govind Babu (Journal of the Scientific Society, 2016)
Introduction: Aflibercept in combination with FOLFIRI has been shown to improve overall survival in the pivotal VELOUR study. Aflibercept has not yet been marketed in India. Sanofi has made available this drug for Indian patients under a program called Named Patient Access Program (NPP). We present a limited clinical experience with the use of aflibercept at our center. Materials and Methods: We analyzed the data of the patients who received aflibercept under NPP. Aflibercept was given in combination with FOLFIRI as second-line for patients who progressed on oxaliplatin based therapy. Aflibercept was given at 4 mg/kg intravenous (IV) every 15 days. Chemotoxicities were assessed as per CTCAE. Response evaluation was done every four cycles. Results: Five patients were enrolled. The median age was 34 years. The median number of aflibercept cycles administered was 12. Common grade 2/3 toxicities were mucositis, diarrhea, neutropenia thrombocytopenia, and hypertension seen in three (60%), three (60%), two (40%), two (40%), and one patient respectively. After four cycles, the response was assessed as: One complete remission (CR), three partial remissions (PR), and one progressive disease (PD). Three patients completed 12 cycles of chemotherapy and aflibercept. At the end of 12 cycles, one patient still in CR and two patients were in PR. Four patients were alive till date. Conclusion: As we had very less number of patients, it was very difficult to compare it with VELOUR data. It is one of option as second-line in metastatic colorectal cancer (mCRC) who progressed on oxaliplatin chemotherapy. Mucositis, diarrhea, and hematological toxicity were the most common toxicity in our patient.